Application of 2D modeling in simulation the erosion of dykes on Thach Han river basin in Vietnam - D.Q. Tri; T.H. Thai; N.T.M. Linh (Lowland Technology International, 2018)
Application of 2D modeling to carrying out research on the calculation of water flow rate and the amount of sediments transported has been proved effectively. In this paper, the hydraulic model MIKE 21 was applied to calculate and simulate the data of two big flood events in 1999 and 2005. The calibrated and validated results at Thach Han station and Dong Ha station were relatively similar in terms of phases and amplitude fluctuations of water level with the high value of NashSutcliffe coefficient, and low value of RMSE-observations standard deviation ratio (RSR) and Percent bias (PBIAS). The hydraulic modeling and sediment transport were applied by using MIKE 21 gave an overall assessment on the erosion process on the Thach Han River Basin and river bottom before and after the construction of the dikes and embankments. The construction, accordingly, has proven its significant effects on alleviating the development of increasing erosion on parts of the river flowing through Trieu Do commune, Quang Tri province, Vietnam.